Progress in application of mesenchymal stem cells in treatment of acute myocardial infarction - JIANG Yu, QIAN Haiyan (Jichu yixue yu linchuang, 2023)
Acute myocardial infarction (AMI) is an ischemic myocardial necrosis caused by coronary artery occlusion, which can't be self-repaired through cardiomyocyte regeneration. The necrotic myocardium is replaced by fibrous scars during ventricular remodeling, ultimately leading to heart failure. The safety and efficacy of mesenchymal stem cells (MSCs) transplantation after AMI have been demonstrated by numerous preclinical and clinical studies. MSCs are composed of heterogeneous cells with multi-directional differentiation potential, which can regulate oxidative stress, and secrete a variety of cytokines and growth factors. After being implanted in vivo, MSCs play their roles in immunomodulatory, angiogenesis, anti-inflammatory, and anti-apoptosis through trans-differentiation, cell fusion, and paracrine. Currently, there has been a variety of access to implant MSCs, including intramyocardial injection, intracoronary infusion, and intravenous injection. In addition, the dose and timing of transplantation are also important factors affecting the therapeutic effect of MSCs. However, the low retention and survival rates of MSCs in infarcted myocardium after being transplanted limit their further effect and hinder their clinical translation. In recent years, new concepts, strategies, technologies, and methods for MSCs treatment have been proposed, including cell preconditioning, optimization of the infract local microenvironment, combined gene therapy or tissue engineering technology, exosome infusion, and targeted transplantation of stem cells and their exosomes, which significantly improve the transplantation efficiency and therapeutic effect of MSCs, and open a new chapter for the research and transformation of stem cells to repair the infarcted myocardium. This article reviews the progress of MSCs in repairing myocardial infarction in recent years.